Ligand and structure-based approaches for the exploration of structure–activity relationships of fusidic acid derivatives as antibacterial agents - Zheng, Wende; Tu, Borong; Zhang, Zhen; Li, Jinxuan; Yan, Zhenping; Su, Kaize; Deng, Duanyu; Sun, Ying; Wang, Xu; Zhang, Bingjie; Zhang, Kun; Wong, Wing-Leung; et al. (Frontiers in Chemistry, 2023)
Fusidic acid (FA) has been widely applied to the clinical prevention and treatment of bacterial infections. Nonetheless, its clinical application has been limited due to its narrow antimicrobial spectrum and some side effects. Therefore, it is necessary to explore the structure-activity relationships of FA derivatives as antibacterial agents to develop novel ones possessing a broad antimicrobial spectrum. Firstly, the pharmacophore model was established on the nineteen FA derivatives with remarkable antibacterial activities reported in previous studies. The common structural characteristics of the pharmacophore emerging from the FA derivatives were determined as those of six hydrophobic centres, two atom centres of the hydrogen bond acceptor, and a negative electron centre around the C-21 field. Then, seven FA derivatives have been designed according to the reported structure-activity relationships and the pharmacophore characteristics. The designed FA derivatives were mapped on the pharmacophore model and the Qfit values of all FA derivatives were over 50 and FA-8 possessed the highest value of 82.66. The molecular docking studies of the partial target compounds were conducted with the elongation factor G (EF-G) of S. aureus. Furthermore, the designed FA derivatives have been prepared and their antibacterial activities were evaluated by the inhibition zone test and the minimum inhibitory concentration (MIC) test. The derivative FA-7 with chlorine group as substituent group at C-25 of FA displayed the best antibacterial property with MIC of 3.125 µM. Subsequently, 3D-QSAR was carried on all the derivatives by using the CoMSIA mode of SYBYL-X 2.0. Hence, a computer-aid drug design model was developed for FA, which can be further used to optimize FA derivatives as highly potent antibacterial agents.